BLUE ECONOMY ANALYSIS IN THE PERSPECTIVE OF MAQASHID SHARIA FOR SUSTAINABLE ECONOMIC DEVELOPMENT - Surotul Lubna; Yuliatin (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2026)
The Blue Economy has emerged as a global framework for promoting sustainable utilization of marine and ocean resources to support economic growth, environmental preservation, and social welfare. However, the framework is often criticized for its limited ethical foundation, as it is largely driven by technocratic and economic considerations. In contrast, Islamic economics offers a comprehensive value-based system rooted in the principles of tawhid (oneness of God), khalifah (stewardship), amanah (trust), justice (‘adl), and maslahah (public welfare). This study aims to analyze the Blue Economy from the perspective of Islamic economics by examining its conceptual compatibility and potential implementation within an Islamic ethical framework. This research employs a qualitative approach using library research methods. Data are collected from secondary sources, including academic journals, books, and reports from international organizations such as the United Nations Environment Programme (UNEP), the World Bank, and the Food and Agriculture Organization (FAO). The data are analyzed using descriptive-analytical and content analysis techniques to identify the convergence between Blue Economy principles and Islamic economic values. The findings show that there is a strong conceptual alignment between the Blue Economy and Islamic economics, particularly in terms of sustainability, environmental stewardship, and intergenerational justice. The principle of mizan (balance) in Islam closely corresponds with ecological sustainability in the Blue Economy. Furthermore, maqasid al-shariah provides an ethical foundation for evaluating marine economic activities, ensuring the protection of life, wealth, and environmental integrity. The study also finds that Islamic financial instruments such as zakat, waqf, and sukuk can be utilized to support the implementation of sustainable marine development. In conclusion, the integration of the Blue Economy and Islamic economics offers a holistic framework that combines economic efficiency, environmental sustainability, and moral responsibility. This integrated approach is particularly relevant for Muslim-majority countries such as Indonesia, which possess vast marine resources and a strong Islamic value system.